2003
DOI: 10.1152/jn.01179.2002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Architecture of Eye Position Gain Fields in Visual Association Cortex of Behaving Monkey

Abstract: In the behaving monkey, inferior parietal lobe cortical neurons combine visual information with eye position signals. However, an organized topographic map of these neurons' properties has never been demonstrated. Intrinsic optical imaging revealed a functional architecture for the effect of eye position on the visual response to radial optic flow. The map was distributed across two subdivisions of the inferior parietal lobule, area 7a and the dorsal prelunate area, DP. Area 7a contains a representation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
76
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 33 publications
(53 reference statements)
10
76
0
Order By: Relevance
“…Optical imaging of changes in the oxygenation of hemoglobin within and across the cortical surface permits the evaluation of global neuronal network activity (Malonek and Grinvald, 1996). Area 7a and the dorsal prelunate (DP) area, two gyral portions of the inferior parietal lobule, are accessible to direct visualization for intrinsic optical imaging (Siegel et al, 2003). Area 7a, which lies close to the intraparietal sulcus, is modulated by the inferior, contralateral position of the eye in the orbit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical imaging of changes in the oxygenation of hemoglobin within and across the cortical surface permits the evaluation of global neuronal network activity (Malonek and Grinvald, 1996). Area 7a and the dorsal prelunate (DP) area, two gyral portions of the inferior parietal lobule, are accessible to direct visualization for intrinsic optical imaging (Siegel et al, 2003). Area 7a, which lies close to the intraparietal sulcus, is modulated by the inferior, contralateral position of the eye in the orbit.…”
Section: Introductionmentioning
confidence: 99%
“…The neighboring DP represents the superior, contralateral eye position. A push-pull relationship between these two areas suggests that they may have a distributed representation of the position of the eye (Siegel et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The ISOI studies also suggested that the rebound was more spatially diffuse and less stimulus-specific than the initial dip (4,7,10). The initial dip thus became the signal of choice in a number of functional imaging studies, not only in ISOI (11)(12)(13)(14)(15) but also in fMRI (16).…”
mentioning
confidence: 98%
“…This has not yet been systematically attempted. However, in parietal areas 7a and DP, Siegel and coworkers have used a peripheral detection task to uncover topographic representations of the contralateral hemifield with intrinsic optical imaging (22)(23)(24).In this study, we mapped the functional and topographic organization of macaque LIP using BOLD fMRI in two macaques performing a demanding rapid serial visual presentation (RSVP) search task. The task does not address the relative roles of LIP in oculomotor planning and the allocation of spatial attention.…”
mentioning
confidence: 99%
“…This has not yet been systematically attempted. However, in parietal areas 7a and DP, Siegel and coworkers have used a peripheral detection task to uncover topographic representations of the contralateral hemifield with intrinsic optical imaging (22)(23)(24).…”
mentioning
confidence: 99%